Comparison on the effect of different dressings on poor wound healing after surgery via posterior midline approach (不同敷料对后正中手术入路切口愈合不良的影响差异研究) - ZHANG Tingting (张婷婷); ZHANG Hongyang (张宏扬); ZHU Ruifang (朱瑞芳) (中西医结合护理)
Objective The purpose of this study was to compare the effects of different dressings on poor wound healing in patients undergoing surgery via posterior midline approach. Methods A total of 60 patients who underwent surgery via posterior midline approach in the pediatric ward of Neurosurgery Center of Tiantan Hospital were included as research objects. All pediatric patients were divided into control group and intervention group by using random number table method. The pediatric patients in the control group (30 cases) were protected by standard wound dressings starting from the first dressing change after surgery, while the pediatric patients in the intervention group (30 cases) were received intervention (silver alginate ion dressing + hydrocolloid dressing protection) starting from the first dressing change after surgery. The incisions of all pediatric patients were examined daily starting from the first day post-surgery to assess postoperative wound healing, and frequency of dressing changes during the healing process was recorded. Results The healing time of incision grade A in the intervention group was significantly shorter than that in the control group［(12. 02±1. 69) days vs. (15. 90±2. 30) days］, with a statistically significant difference (P＜0. 01). The number of dressing changes in the intervention group was significantly lower than that in the control group ［(2. 13±0. 99) vs. (3. 05±0. 85)］, with a statistically significant difference (P＜0. 05). Conclusion The utilization of silver alginate + hydrocolloid dressing outperformed traditional dressings in safeguarding against impaired wound healing following a posterior median surgical approach. This intervention not only shorten wound healing time but also reduced the frequency of dressing changes, thereby alleviating pain and promoting prompt wound recovery among pediatric patients. (目的 观察不同敷料对后正中手术入路切口愈合不良的影响差异。方法 选取2021年3月—7月于首都医科大学附属北京天坛医院神经外科中心小儿病区住院期间行后正中入路手术的病例60例, 采用随机数字表法分为对照组和干预组。对照组30例, 即患儿从术后第一次换药时开始仅给予普通敷料保护; 干预组30例, 即患儿从术后第一次换药时开始给予切口干预(藻酸盐银离子敷料+水胶体敷料保护)。从术后第1天开始对所有患儿切口进行检查, 明确术后切口愈合情况, 伤口愈合期间的换药次数, 观察不同敷料对后正中手术入路切口愈合不良的影响差异。结果 术后切口甲级愈合时间干预组(12. 02±1. 69) d, 较对照组(15. 90±2. 30) d缩短, 差异有统计学意义(P＜0. 05); 换药次数干预组(2. 13±0. 99)次, 低于对照组的(3. 05±0. 85) 次, 差异具有统计学意义(P＜0. 01)。结果 给予藻酸盐银离子+水胶体敷料保护对后正中手术入路切口愈合不良的效果优于传统敷料保护, 不仅缩短了切口愈合的时间, 还降低了换药频次, 既减轻了患儿的痛苦, 又促进了切口尽快愈合。)